If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -2x = -16 Solving 4 + -2x = -16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -2x = -16 + -4 Combine like terms: 4 + -4 = 0 0 + -2x = -16 + -4 -2x = -16 + -4 Combine like terms: -16 + -4 = -20 -2x = -20 Divide each side by '-2'. x = 10 Simplifying x = 10
| 8ln(x+5)-5ln(x)= | | 3u^2-8u=3 | | x=23.5 | | 3x+1=-x+7 | | 6x=7x-12 | | 18+2(4+3x)= | | 30+p^2+13p=0 | | v^2-6v+9=2v^2+2v+21 | | x+7x+12x=100 | | 7c-8-6c=-11 | | 0=3x^2-6x-5 | | 30+b^2+b=0 | | x+7x+12x=20x | | 7v^2-42r-49=0 | | 2w+18=4w | | -18=4r+5r | | 2x+[x+2]=144 | | 9y*2=16 | | 12X=1+12 | | 5(2x+3y)-2(2x+5y)= | | -16x^2+60x+3=0 | | 8r^2-40r-112=0 | | 8x-4y=56 | | 3(x-5)-16=2(x-8)+4 | | 6.6(x-1)=-0.4x+28.4 | | -12=3(1+k) | | =(x^4)-32x+56 | | p(x)=3x^5-2x^4+4x^3-7x^2+mx-16 | | 14d=252 | | 25*7.25+x=443.75 | | (2c-4)-(4c-8)= | | 6y+3-y+8= |